Lung Cancer Screening Using Low Dose CT Scanning in Germany: Extrapolation of Results From the National Lung Screening Trial - Stang, Andreas (Dtsch Arztebl Int, 2015)
BACKGROUND: It is now debated whether the screening of heavy smokers for lung cancer with low dose computed tomography (low dose CT) might lower their mortality due to lung cancer. We use data from the National Lung Screening Trial (NLST) in the USA to predict the likely effects of such screening in Germany. METHODS: The number of heavy smokers aged 55–74 in Germany was extrapolated from survey data obtained by the Robert Koch Institute. Published data from the NLST were then used to estimate the likely effects of low dose CT screening of heavy smokers in Germany. RESULTS: If low dose CT screening were performed on 50% of the heavy smokers in Germany aged 55–74, an estimated 1 329 506 persons would undergo such screening. If the screening were repeated annually, then, over three years, 916 918 screening CTs would reveal suspect lesions, and the diagnosis of lung cancer would be confirmed thereafter in 32 826 persons. At least one positive test result in three years would be obtained in 39.1% of the participants (519 837 persons). 4155 deaths from lung cancer would be prevented over 6.5 years, and the number of persons aged 55–74 who die of lung cancer in Germany would fall by 2.6%. 12 449 persons would have at least one complication, and 1074 persons would die in the 60 days following screening. CONCLUSION: The screening of heavy smokers for lung cancer can lower their risk of dying of lung cancer by 20% in relative terms, corresponding to an absolute risk reduction of 0.3 percentage points. These figures can provide the background for a critical discussion of the putative utility of this type of screening in Germany.